Towards a Local Integration of Theories: Codes and Praxeologies in the Case of Computer-Based Instruction - Espinoza-Salfate, L; Barbe-Farre, J (Kluwer Academic Publishers, 2013)
We report on the development of a language of description that facilitates an integrated analysis of classroom video data in terms of the quality of the teaching-learning process and the students access to valued forms of mathematical knowledge. Our research setting is the introduction of software for teachers for improving the mathematical learning in underprivileged classrooms. As theoretical antecedents we draw on the Théorie Anthropologique du Didactique (Chevallard) and the Theory of Pedagogic Codes (Bernstein). We systematically integrate these theories locally. As a result on a meta-theoretical level, a new methodology, consisting of a system of categories, is the product of the local integration of the two theories. © 2012 Springer Science+Business Media B.V.